Onsets and Rimes in a Phonologically Transparent Orthography: Differences between Good and Poor Beginning Readers of Dutch - Geudens, Astrid; Sandra, Dominiek (Brain and language, 1999)
This study investigates whether beginning readers of Dutch develop onset-rime units when these units are emphasized in their reading method, even when the orthography is transparent at the grapheme–phoneme level. The speed of naming intact pseudowords (wot) was compared with the speed of naming pseudowords with an onset-rime (w ot) or body-coda (wo t) segmentation. Whereas body-coda items consistently slowed down naming for both good and poor readers, the onset-rime effect covaried with reading skill: it changed from inhibitory for good readers to facilitatory for poor readers. Two alternative explanations are proposed.